2022
DOI: 10.1182/bloodadvances.2021005998
|View full text |Cite
|
Sign up to set email alerts
|

Six-month antibody persistence after BNT162b2 mRNA COVID-19 vaccination in patients with chronic lymphocytic leukemia

Abstract: Patients with chronic lymphocytic leukemia (CLL) have an impaired antibody response to COVID-19 vaccination. Here, we evaluated SARS-CoV-2S antibody persistence at 6 months after a two-dose regimen of BNT162b2 COVID-19 vaccine in patients with CLL/small lymphocytic lymphoma (SLL) and healthy controls who had a documented initial response, 2-3 weeks after the second vaccine dose. In a total of 61 patients with CLL/SLL and 39 controls, antibodies were still detectable in 90.2% (n555) of the patients compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 6 publications
3
21
1
Order By: Relevance
“…In CLL patients who do respond to vaccination, 36 this remains intact for at least six months. However, among CLL patients who fail to respond to two vaccination doses, the response rates to third or more doses are likely to be low, and with low levels of anti‐S 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CLL patients who do respond to vaccination, 36 this remains intact for at least six months. However, among CLL patients who fail to respond to two vaccination doses, the response rates to third or more doses are likely to be low, and with low levels of anti‐S 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In CLL patients who do respond to vaccination, 36 this remains intact for at least six months. However, among CLL patients who fail to respond to two vaccination doses, the response rates to third or more doses are likely to be low, and with low levels of anti-S. 37 Nevertheless, third and perhaps fourth vaccine doses are the easiest and most immediately available option and supported by our T-cell FluoroSpot data showing a functional T-cell anti-COVID-19 response in ~80% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on SARS‐CoV‐2 vaccination in CLL have evaluated the persistence of SARS‐CoV‐2 antibodies after vaccination. 48 , 49 Tadmor and co‐workers. 48 found that the decline of SARS‐CoV‐2 antibody levels in CLL patients, assessed after a median time of 100 days after vaccination was no different from that of elderly healthy controls.…”
Section: Do Chronic Lymphocytic Leukemia Patients Who Respond To Sars...mentioning
confidence: 99%
“…However, antibody titers declined dramatically with time, and active therapy was linked to a loss of response. 49 …”
Section: Do Chronic Lymphocytic Leukemia Patients Who Respond To Sars...mentioning
confidence: 99%
“…F I G U R E 1 Rate of seroconversion after SARS-CoV-2 mRNA vaccine on pooled meta-analysis in the general population of CLL patients (A), in patients treatment-naïve (B), in patients who had been given an anti-CD20 monoclonal antibody at any time before vaccination (C), patients vaccinated within 12 months from the last infusion of anti-CD20 antibody (D), patients on therapy with BTKi (E), and patients on therapy with venetoclax (F) Identifying subgroups of CLL patients with different responses to SARS-CoV-2 vaccination and antibodies persistence over the time is important to decide treatment strategies and developing studies aimed at improving response to vaccination. 20,21 Recent preliminary results indicate that a third dose ("booster") of SARS-CoV-2 mRNA vaccines induces seroconversion in 42% of the patients seronegative after the second vaccination dose. 17…”
Section: Patients On Therapy With Venetoclax (N = 94)mentioning
confidence: 99%